Success-slope effects on the illusion of control and on remembered success-frequency - Anastasia Ejova; Daniel J. Navarro; Paul H. Delfabbro (Judgment and Decision Making, 2013)
The illusion of control refers to the inference of action-outcome contingency in situations where outcomes are in fact random. The strength of this illusion has been found to be affected by whether the frequency of successes increases or decreases over repeated trials, in what can be termed a ``success-slope'' effect. Previous studies have generated inconsistent findings regarding the nature of this effect. In this paper we present an experiment (N = 334) that overcomes several methodological limitations within this literature, employing a wider range of dependent measures (measures of two different types of illusory control, primary (by self) and secondary (by luck), as well as measures of remembered success-frequency). Results indicate that different dependent measures lead to different effects. On measures of (primary, but not secondary) control over the task, scores were highest when the rate of success increased over time. Meanwhile, estimates of success-frequency in the task did not vary across conditions and showed trends consistent with the broader literature on human memory.